A quantitative neuropathological assessment of translocator protein expression in multiple sclerosis - Nutma,E; Stephenson,JA; Gorter,RP; de,Bruin J; Boucherie,DM; Donat,CK; Breur,M; van,der Valk P; Matthews,P; Owen,D; Amor,S (Brain, 2019)
The 18kDa translocator protein (TSPO) is increasingly used to study brain and spinal cord inflammation in degenerative diseases of the CNS such as multiple sclerosis. The enhanced TSPO PET signal that arises during disease is widely-considered to reflect activated pathogenicmicroglia, although quantitative neuropathological data to support this interpretation has not been available. With the increasing interest in the role of chronic microglial activation in multiple sclerosis, characterising the cellular neuropathology associated with TSPO expression is of clear importance for understanding the cellular and pathological processes on which TSPO PET imaging is reporting.Here we have studied the cellular expression of TSPO and specific binding of two TSPO targeting radioligands ([3H]PK11195 and [3H]PBR28) in tissue sections from 42 multiple sclerosis cases and 12 age-matched controls. Markers of homeostatic and reactive microglia, astrocytes, and lymphocytes were used to investigate the phenotypes of cells expressing TSPO. There was an approximate 20-fold increase in cells double positive for TSPO and human leukocyte antigen -DR in active lesions and in the rim of chronic active lesion, relative to normal appearing white matter. TSPO was uniformly expressed across myeloid cells irrespective of their phenotype, rather than being preferentially associated with pro-inflammatory microglia or macrophages. TSPO+astrocytes were increased up to 7-fold compared to normal appearing white matter across all lesion sub-types and accounted for 25% of the TSPO+ cells in these lesions. To relate TSPO protein expression to ligand binding, specific binding of the TSPO ligands [3H]PK11195 and [3H]PBR28was determined in the same lesions. TSPO radioligand binding was increased up to seven times for [3H]PBR28 and up to two times for [3H]PK11195 in active lesions and the centre of chronic ac